Modeling and Engine Performance of Direct Injection Hydrogen Fueled Engine - M. M., Rahman; M. M., Noor; R. A., Bakar; K., Kadirgama (2009)
The present study explores the modeling of four cylinder direct injection hydrogen fueled engine and investigates the effect of engine speed on engine performance. GTPower was utilized to develop the model for direct injection engine. Air-fuel ratio was varied from rich limit (AFR=27.464) to a lean limit (AFR=171.65). The rotational speed of the engine was varied from 1000 to 6000 rpm. It can be seen from the obtained results that the engine speed are greatly influence on the brake mean effective pressure (BMEP), brake specific fuel consumption (BSFC). It can be seen that the decreases of BMEP with increases of engine speed, however, increases the brake specific fuel consumption. For rich mixtures (low AFR), BMEP decreases almost linearly, then decreases it with a non-linear manner. It can be observed that the brake thermal efficiency increases nearby the richest condition and then decreases with increases of engine speed. The optimum minimum value of BSFC occurred within a range of AFR from 38.144 (φ = 0.9) to 49.0428 (φ = 0.7) for the selected range of speed. It can be seen that higher volumetric efficiency emphasizes that direct injection of hydrogen is a strong candidate solution to solve the problem of the low volumetric efficiencies of hydrogen engine. Maximum brake torque speed for hydrogen engine occurs at lower speed compared with gasoline. The present contribution suggests the direct injection fuel supply system as a strong candidate for solving the power and abnormal combustion problems.